2014
DOI: 10.1111/bph.12702
|View full text |Cite
|
Sign up to set email alerts
|

In vivo opioid receptor heteromerization: where do we stand?

Abstract: to correct some mis-citations in text and tables, these are marked by an asterisk.Opioid receptors are highly homologous GPCRs that modulate brain function at all levels of neural integration, including autonomous, sensory, emotional and cognitive processing. Opioid receptors functionally interact in vivo, but the underlying mechanisms involving direct receptor-receptor interactions, affecting signalling pathways or engaging different neuronal circuits, remain unsolved. Heteromer formation through direct physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 134 publications
1
35
0
Order By: Relevance
“…Interestingly, in the above studies μ‐ORs were found to crystallize as dimers . Largely based on previous experiments applying resonance energy transfer methods, these findings support the hypothesis that μ‐ORs might form homodimers . However, the nanoscale organization and dynamics of μ‐ORs on the surface of living cells remain largely unknown, mostly due to technical limitations of conventional methods.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Interestingly, in the above studies μ‐ORs were found to crystallize as dimers . Largely based on previous experiments applying resonance energy transfer methods, these findings support the hypothesis that μ‐ORs might form homodimers . However, the nanoscale organization and dynamics of μ‐ORs on the surface of living cells remain largely unknown, mostly due to technical limitations of conventional methods.…”
Section: Introductionsupporting
confidence: 71%
“…Opioid receptors (ORs) belong to the family A of rhodopsin‐like G protein‐coupled receptors and occur in three major subtypes, μ, δ and κ . They are predominantly found in the central and peripheral nervous system, where they modulate transmission and perception of pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular and pharmacological activities of the MOP receptor are modulated by other GPCR systems (2)(3)(4)(5). In some case, such heterologous regulation involves receptor heteromerization (6), which is considered to confer new binding and endocytosis properties to the complex and/or to promote novel signaling pathways or, conversely, to impair signal transduction (7,8). The heteromerization of the MOP receptor with other opioid receptors, DOP, KOP, and NOP (9 -12) or with non-opioid receptors such as ␣ 2 -adrenergic (13)(14)(15), somatostatin SST 2A (16) or substance P NK1 (17) receptors has been reported.…”
mentioning
confidence: 99%
“…Such heteromers would represent the molecular determinant that underlies the integrated changes observed at system level. However, mu-delta in vivo co-expression and heteromerization remain extremely difficult to tackle with existing tools [11] . In vivo co-localization has indeed only been reported in dorsal root ganglia (DRG) [1214] , spinal cord [15] and within a limited number of brain areas [1618] but, as for most GPCRs, we still miss in-depth anatomical mapping of opioid receptors in the brain that also provides subcellular resolution.…”
mentioning
confidence: 99%